2020
DOI: 10.1021/acssuschemeng.9b05317
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Biomimetic Hydrogels from Silk Fibroin and Nanocellulose

Abstract: Biomimetic hydrogels offer a new platform for hierarchical structure controlled tough, biocompatible, mechanically tunable and printable gels for regenerative medicine. Herein we report for the first time, the detailed effects of various kinds of nanocellulose namely, bacterial nanocellulose (BC), cellulose nanofibers (CNF) and cellulose nanocrystals (CNC) on the morphology, structure-property relationship and 3D printability of the photochemically crosslinked regenerated silk fibroin (RSF)/nanocellulose compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 85 publications
1
68
0
Order By: Relevance
“…A range of functional additives can be used to enhance the mechanical performance of the Ru(II)/persulfate-mediated photo-crosslinked silk fibroin hydrogels, including resilin, graphene oxide (GO), and cellulose [ 59 , 70 , 72 , 73 ]. Resilin is one of the most resilient (~92%) proteins, responsible for the jumping and flight of many insects [ 62 , 74 ].…”
Section: Photo-oxidizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of functional additives can be used to enhance the mechanical performance of the Ru(II)/persulfate-mediated photo-crosslinked silk fibroin hydrogels, including resilin, graphene oxide (GO), and cellulose [ 59 , 70 , 72 , 73 ]. Resilin is one of the most resilient (~92%) proteins, responsible for the jumping and flight of many insects [ 62 , 74 ].…”
Section: Photo-oxidizationmentioning
confidence: 99%
“…Cellulose is sustainable and offers superior mechanical strength [ 70 ] and has been used as a useful additive for 3D printing [ 84 ]. The addition of bacterial cellulose dramatically increased the toughness of photo-crosslinked silk-cellulose composites to 108 kJ m −3 , six-fold higher than monolithic silk fibroin hydrogels (around 16.7 kJ m −3 ).…”
Section: Photo-oxidizationmentioning
confidence: 99%
“…Dorishetty et al presented biomimetic silk fibroin/cellulose hydrogels for a wide range of tissue engineering applications, including cartilage and meniscus, due to the achieved mechanical properties. For this purpose, the authors investigated the effect of different types of nanocellulose, such as bacterial nanocellulose and cellulose nanofibers, on morphology, structure and performances of the composite hydrogels [ 86 ].…”
Section: Recent Advances On the Development Of Silk Fibroin-based mentioning
confidence: 99%
“…Recently, Dorishetty et al reported for the first time the detailed effects of various kinds of nanocellulose, namely, BC, CNF, and CNC on the morphology, structure–property relationship, and 3D printability of the photochemically cross-linked SF/nanocellulose composite hydrogels. Results indicated that SF/BC composite hydrogel possessed the superior mechanical performance among the hydrogels (Dorishetty et al 2020 ). However, it has been found that clogging is experienced when pastes of cellulose nanofibers are used at high concentration (> 0.8%) in 3D printing, due to the large bunches of fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Dorishetty et al developed the SF/BC inks which could achieve a maximum cellulose content of about 5 wt% and could only print two layers structure. Higher resolution with 3D stereoscopic construct was difficult to achieve due to limited cellulose in inks (Dorishetty et al 2020 ). Because TEMPO-mediated oxidation helps reduce the adhesion and provide electrostatic repulsions between microfibrils by introducing certain amount of carboxylate groups, which facilitates the dispersion of cellulose nanofibers, especially BC.…”
Section: Introductionmentioning
confidence: 99%